Aktualisasi Metode Sosio-Drama Sejarah untuk Melatih Kemampuan Berpikir Sejarah: Representasi Pendekatan Transformatif - Dyah Kumalasari; Ita Mutiara Dewi; Roro Wilis; Rahayu Fuji Astuti (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
A history curriculum dominated by a single narrative tends to ignore the importance of source analysis, context, and causal relationships in history. This study aims to analyze the implementation of the socio-drama method as a representation of a transformative approach to training historical thinking skills. This study uses a qualitative approach with a single case study design at SMA Negeri 6 Yogyakarta. The subjects of this study were the 11th grade history teacher and 6 11th grade students. Data collected through in-depth interviews, direct observation, document studies, and enriched literature studies were analyzed using the Miles and Huberman interactive model. This study produced three important findings, including: (1) The socio-drama model was implemented through three main stages, namely the pre-conception stage, collaborative inquiry, and socio-drama staging stage. To ensure collaboration, there was a division of roles in the form of scriptwriter, narrator, actor, and director adjusted to the characteristics of the students; and (2) Students' perspectives on history changed from rote learning to meaning making; and (3) Implications for historical thinking skills were demonstrated through chronological thinking skills, historical understanding, analysis and interpretation, and historical research skills. The contribution of this research can be a reference for history teachers to develop a transformative approach in history learning, especially training historical thinking skills in order to improve the quality of learning.